2021
DOI: 10.1016/j.isci.2021.103148
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic and transcriptional responses underlying mangrove adaptation to UV-B

Abstract: Summary Tropical plants have adapted to strong solar ultraviolet (UV) radiation. Here we compare molecular responses of two tropical mangroves Avecennia marina and Rhizophora apiculata to high-dose UV-B. Whole-genome bisulfate sequencing indicates that high UV-B induced comparable hyper- or hypo-methylation in three sequence contexts (CG, CHG, and CHH, where H refers to A, T, or C) in A. marina but mainly CHG hypomethylation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 97 publications
0
5
0
Order By: Relevance
“…Latest findings on mangrove responses to UV radiation revealed that A. marina undergoes stringent silencing of TEs upon UV-B exposure. Contrary to this, a relaxation of TE silencing is observed in R. apiculata ( Wang et al., 2021 ). To conclude, mangrove genomes adjust TE load to an optimal range to attain epigenetic control over adaptive responses.…”
Section: Epigenetics Of Mangrove Adaptations To Intertidal Environmentsmentioning
confidence: 65%
“…Latest findings on mangrove responses to UV radiation revealed that A. marina undergoes stringent silencing of TEs upon UV-B exposure. Contrary to this, a relaxation of TE silencing is observed in R. apiculata ( Wang et al., 2021 ). To conclude, mangrove genomes adjust TE load to an optimal range to attain epigenetic control over adaptive responses.…”
Section: Epigenetics Of Mangrove Adaptations To Intertidal Environmentsmentioning
confidence: 65%
“…Epigenetic control of TEs usually changes the expression of neighboring genes that may then cause phenotypic plasticity, which affects adaptive responses of mangroves to the harsh environment. It has been shown before that DNA methylation plays an important role in response of mangrove species to abiotic stresses such as high UV-B (Wang et al, 2021b). In addition, UV-B induced relaxation of TE silencing and therefore up-regulation of the TE-neighboring genes in mangrove species was reported which led to the conclusion of divergent clue behind UV-B adaptation at both the epigenetic and transcriptional level (Wang et al, 2021b).…”
Section: Dna Methylation and Stress-response In Mangrovesmentioning
confidence: 99%
“…It has been shown before that DNA methylation plays an important role in response of mangrove species to abiotic stresses such as high UV-B (Wang et al, 2021b). In addition, UV-B induced relaxation of TE silencing and therefore up-regulation of the TE-neighboring genes in mangrove species was reported which led to the conclusion of divergent clue behind UV-B adaptation at both the epigenetic and transcriptional level (Wang et al, 2021b). Recent transcriptional studies also have reported that in mangrove populations growing next to the ocean under high salinity various epigenetic regulation genes are differentially expressed along with upregulated stress response genes (Miryeganeh and Saze, 2021a, b).…”
Section: Dna Methylation and Stress-response In Mangrovesmentioning
confidence: 99%
“…Additionally, recent developments in genome editing techniques, like CRISPR-based systems, have the capacity to change DNA methylation patterns in a precise way. Breeders may be able to improve UVB tolerance in crops by modifying the DNA methylation status of particular genes or regulatory regions [ 16 , 86 ]. However, it is crucial to take into account the legal and moral implications of using genome editing methods in crop breeding.…”
Section: Potential Strategies For Breeding Uvb-resistant Plantsmentioning
confidence: 99%